The Effect of Brand Image, Lifestyle, Electronic Word Of Mouth on Oppo Smartphone Purchase Decisions(Case study on Students in Semarang City) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
The development of digital technology has brought major changes in consumer behavior, including in online shopping activities. One of the phenomena that arises as a result of this change is impulse buying, which is spontaneous purchasing behavior without planning. Beauty products such as Somethinc are one of the categories that are often bought impulsively, especially through e- Commerce platforms with various digital marketing strategies such as sales promotion, flash sales, live streaming, and online customer reviews. This study aims to analyze the influence of sales promotion, flash sales, live streaming, and online customer reviews on impulse buying of Somethinc products. This study uses a quantitative approach with a causal design. The sampling technique used is non- probability sampling with the purposive sampling method. The number of respondents was 106 people who were users of Somethinc products in Semarang City. Data were collected using an online questionnaire and analyzed using multiple linear regression techniques using IBM SPSS Statistics 27 software. The results of the study showed that partially sales promotion had no effect on impulse buying. Meanwhile, flash sales, live streaming, and online customer reviews have a positive and significant effect on impulse buying. Simultaneously, the four independent variables have a significant effect on impulse buying. These findings suggest that certain digital marketing strategies can trigger consumer impulse buying behavior, especially through aspects of interaction and trust built online.
Keywords: Sales Promotion; Flash Sale; Online Customer Reviews